Ribosome assembly in trypanosomatids: A novel therapeutic target - Kamina, Anyango D. (Trends Parasitol, 2016)
In Liu et al., the authors present a 2.5-Å structure of the Trypanosoma cruzi 60S ribosomal subunit and propose a model for the stepwise assembly of the large subunit ribosomal RNA (rRNA). Based on this study, we discuss how the unique features of trypanosomatid ribosome assembly offer potential drug targets.